How Islamic Social Finance Boosts Psychological Well-Being? - Cahyanti, Irni Sri; Ulfah, Ulfah; Suhendi, Endi (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
While the economic impact of Islamic social finance (ISF) is increasingly acknowledged, its potential contribution to psychological well-being remains underexplored. This study investigates the relationship between ISF practices (Zakat, Infaq, Sadaqah, Waqf) and psychological well-being. Using a qualitative descriptive approach, the study undertakes a comprehensive review of existing literature, encompassing books and national and international journal articles. Findings demonstrate a strong correlation between ISF and various dimensions of psychological well-being, including self-acceptance, positive relationships, autonomy, environmental mastery, life goals, and self-development. This positive association is attributed to ISF's central role in achieving Falah (spiritual prosperity) within the maqashid al-sharia (objectives of Islamic law) framework, fostering social justice and shared prosperity conducive to individual well-being. The study recommends that philanthropic institutions prioritize enhancing service quality in collecting and distributing ISF funds to maximize their positive impact on psychological well-being within the community.========================================================================================================ABSTRAK – Bagaimana Keuangan Sosial Syariah Meningkatkan Kesejateraan Psikologis? Meskipun dampak ekonomi keuangan sosial syariah (KSS) semakin diakui, potensinya terhadap kesejahteraan psikologis masih belum banyak dieksplorasi. Studi ini bertujuan untuk mengkaji hubungan antara praktik KSS (Zakat, Infak, Sedekah, Wakaf) dengan kesejahteraan psikologis. Dengan pendekatan deskriptif kualitatif, studi ini melakukan tinjauan literatur yang komprehensif dengan menganalisis sejumlah buku dan artikel, baik dari jurnal nasional maupun internasional. Temuan menunjukkan hubungan yang erat antara KSS dan berbagai dimensi kesejahteraan psikologis, meliputi penerimaan diri, hubungan positif, otonomi, penguasaan lingkungan, tujuan hidup, dan pengembangan diri. Hubungan positif ini tidak terlepas dari peran sentral KSS dalam mencapai Falah (kesejahteraan spiritual) dalam kerangka maqashid al-syariah (tujuan hukum Islam), mendorong keadilan sosial, dan meningkatkan kemakmuran bersama yang kondusif bagi kesejahteraan individu. Studi ini merekomendasikan agar lembaga filantropi memprioritaskan peningkatan kualitas layanan dalam pengumpulan dan pendistribusian dana KSS untuk memaksimalkan dampak positifnya terhadap kesejahteraan psikologis masyarakat.